(untitled) (Eurasian Medical Research Periodical, 2023)
Arteriovenous malformation (AVM) is a congenital vascular disease of the brain, manifested by the connection of arteries, veins and small vessels, randomly intertwined with each other, leading to a violation of blood circulation in the affected organ. Veins and arteries have a specific kind of "tangle" of vessels, which is the core of the malformation, interconnected by shunts or fistulas. The most common are brain arteriovenous malformations.